2022
DOI: 10.29137/umagd.1015985
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Behavior of Reinforced Concrete Beams with Different Cold Joint Details

Abstract: Mevcut çalışmada betonarme kirişlerde soğuk derz tipi birleşimin kiriş eğilme davranışı üzerindeki etkileri araştırılmıştır. Bu kapsamda toplam yedi adet kirişin dört nokta eğilme testleri gerçekleştirilmiştir. Bu kirişler 150 mm genişliğe, 300 mm yüksekliğe ve 3000 mm uzunluğa sahiptir. Soğuk derzler üç farklı yöntem ile oluşturulmuştur. Bunlardan ilk ikisi kirişin tam ortasında yani sabit moment bölgesinde yatayla 45 ve 90° açı yapacak şekilde iken, sonuncusu ise kiriş yarı yüksekliği seviyesinde kiriş uzunl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…Additionally, the use of intermediate reinforcement is recommended for cast-in-place construction to address potential cold joints between the wall and coupling beam concrete (Parra-Montesinos et al, 2017). Akın at al(2022) studied flexural behavior of reinforced concrete beams with different cold joint details and found no significant effect from the view of bending capacity.Rao Kishen et al (2007), tested beams with the cold joint interface between concretes with different mixtures on both sides and were subjected to a bending test from three points to obtain fracture parameters. As a result, they found that the compressive strength of concrete poured later should not be much different from the main concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the use of intermediate reinforcement is recommended for cast-in-place construction to address potential cold joints between the wall and coupling beam concrete (Parra-Montesinos et al, 2017). Akın at al(2022) studied flexural behavior of reinforced concrete beams with different cold joint details and found no significant effect from the view of bending capacity.Rao Kishen et al (2007), tested beams with the cold joint interface between concretes with different mixtures on both sides and were subjected to a bending test from three points to obtain fracture parameters. As a result, they found that the compressive strength of concrete poured later should not be much different from the main concrete.…”
Section: Introductionmentioning
confidence: 99%